2019
DOI: 10.1111/fcp.12452
|View full text |Cite
|
Sign up to set email alerts
|

High glucose induced calcium overload via impairment of SERCA/PLN pathway and mitochondrial dysfunction leads to oxidative stress in H9c2 cells and amelioration with ferulic acid

Abstract: Oxidative stress and associated complications are the major pathological concerns of diabetic cardiomyopathy (DC). We aim to elucidate the mechanisms by which high glucose (HG) induced alteration in calcium homeostasis and evaluation of the beneficial effect of two concentrations (10 and 25 μm) of ferulic acid (FA). HG was induced in H9c2 cardiomyoblast by treating with glucose (33 mm) for 48 h, and FA was co‐treated. Intracellular calcium ([Ca2+]i) overload was found increased significantly with HG. For eluci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…In a doxorubicin induced cardiotoxicity model, ferulic acid inhibits cardiac apoptosis and oxidative stress via regulation of MAPK activation, NF-κB pathway and PI3K/Akt/mTOR impairment (Sahu et al, 2019). Lastly, ferulic acid ameliorates high glucose-induced oxidative stress and calcium overload via modulation of the mitochondrial function and SERCA/PLN pathway in H9c2 cardiomyoblast (Salin Raj et al, 2019).…”
Section: Ferulic Acidmentioning
confidence: 92%
“…In a doxorubicin induced cardiotoxicity model, ferulic acid inhibits cardiac apoptosis and oxidative stress via regulation of MAPK activation, NF-κB pathway and PI3K/Akt/mTOR impairment (Sahu et al, 2019). Lastly, ferulic acid ameliorates high glucose-induced oxidative stress and calcium overload via modulation of the mitochondrial function and SERCA/PLN pathway in H9c2 cardiomyoblast (Salin Raj et al, 2019).…”
Section: Ferulic Acidmentioning
confidence: 92%
“…In cardiac H9C2 cells, gallic acid was found to suppress hypertrophy and fibrosis by regulating JNK2 signaling and Smad3 binding. In these cells, ferulic acid was also shown to protect cardiomyoblasts from high glucose induced oxidative stress by mediating Ca 2+ homeostasis (68). Similarly, epigallocatechin-3-gallate mediated cardioprotection was observed through Akt/GSK-3β/caveolin signaling (69).…”
Section: Natural Polyphenols: Therapeutics Of Dcmmentioning
confidence: 99%
“…Besides ARPE-19 cells, FA increases cell viability and reduces apoptosis of hepatocytes and cardiomyocytes exposed to HG ( Song et al, 2016 ). FA improves HG-induced oxidative stress in H9C2 cells ( Salin Raj, Swapna & Raghu, 2019 ). Mechanistically, we found that FA can prevent HG-induced increase in BAX (pro-apoptosis) and decrease in Bcl-2 (anti-apoptosis).…”
Section: Discussionmentioning
confidence: 99%